First study of the two-body scattering involving charm hadrons - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akbar, Z.; et al. (American Physical Society, 2022)
This article presents the first measurement of the interaction between charm hadrons and nucleons. The two-particle momentum correlations of $\mathrm{p}{\mathrm{D}}^{\ensuremath{-}}$ and ${\overline{\mathrm{p}}\mathrm{D}}^{+}$ pairs are measured by the ALICE Collaboration in high-multiplicity pp collisions at $\sqrt{s}=13\text{ }\text{ }\mathrm{TeV}$. The data are compatible with the Coulomb-only interaction hypothesis within $(1.1--1.5)\ensuremath{\sigma}$. The level of agreement slightly improves if an attractive nucleon $(\mathrm{N})\overline{\mathrm{D}}$ strong interaction is considered, in contrast to most model predictions which suggest an overall repulsive interaction. This measurement allows for the first time an estimation of the 68% confidence level interval for the isospin $\mathrm{I}=0$ inverse scattering length of the $\mathrm{N}\overline{\mathrm{D}}$ state ${f}_{0,\mathrm{I}=0}^{\ensuremath{-}1}\ensuremath{\in}[\ensuremath{-}0.4,0.9]\text{ }\text{ }{\mathrm{fm}}^{\ensuremath{-}1}$, assuming negligible interaction for the isospin $\mathrm{I}=1$ channel.
Keywords: Physics; Isospin; Hadron; Particle physics; Multiplicity (mathematics); Nucleon; Charm (quantum number); Coulomb; Scattering; Inverse; Nuclear physics; Quantum mechanics; Geometry; https://purl.org/pe-repo/ocde/ford#1.03.03